Fasciclin-Like Arabinogalactan-Protein 16 (FLA16) Is Required for Stem Development in Arabidopsis - Liu, Edgar; MacMillan, Colleen P.; Shafee, Thomas; Ma, Yingxuan; Ratcliffe, Julian; van de Meene, Allison; Bacic, Antony; Humphries, John; Johnson, Kim L. (Frontiers in Plant Science, 2020)
The predominant Fascilin 1 (FAS1)-containing proteins in plants belong to the Fasciclin-Like Arabinogalactan-protein (FLA) family of extracellular glycoproteins. In addition to FAS1 domains, these multi-domain FLA proteins contain glycomotif regions predicted to direct addition of large arabinogalactan (AG) glycans and many contain signal sequences for addition of a glycosylphosphotidinositol (GPI)-anchor to tether them to the plasma membrane. FLAs are proposed to play both structural and signalling functions by forming a range of interactions in the plant extracellular matrix, similar to FAS1-containing proteins in animals. FLA group B members contain two FAS1 domains and are not predicted to be GPI-anchored. None of the group B members have been functionally characterised. Also, their sub-cellular location has been unresolved, and presence in the cell wall, apoplastic space, plasma-membrane, cytoplasm, or vesicles have implications for understanding their function. We investigated the group B FLA16 in Arabidopsis that is predominantly expressed in inflorescence tissues. FLA16 is the most highly expressed FLA in the stem after Group A members FLA11 and FLA12 that are stem specific. A FLA16 reporter showed expression in cells with secondary cell walls, and FLA16 displayed characteristics of cell wall glycoproteins with moderate glycosylation. Investigation of a fla16 mutant showed loss of FLA16 leads to reduced stem length and altered biomechanical properties, likely as a result of reduced levels of cellulose. Immuno-labelling indicated support for FLA16 location to the plasma-membrane and (apoplastic) cell wall of interfascicular stem fibres cells. Together these results indicate a role for two-FAS1 domain FLAs in plant secondary cell wall synthesis and function.